Women’s knowledge and participation in early detection of cervical cancer: a cross-sectional study - Elia Ika Rahmawati; Dini Andriyani; Fathiyatur Rohmah (Journal of Health Technology Assessment in Midwifery, 2020)
Cervical cancer is a malignant disease that remains a major cause of morbidity and mortality among women in the world. In Indonesia, only 5% of women of reproductive age screen for cervical cancer. 76.6% of cervical cancer patients are detected with the disease when they entered the advanced stage. Early detection of cervical cancer is the key intervention in the reduction of incidence and mortality of cervical cancer. Other studies reported that the awareness of women of reproductive age to do cervical cancer screening is still very low due to a lack of knowledge about cervical cancer. This study aimed to determine the correlation of knowledge and participation in early detection of cervical cancer in women in reproductive age. This study used an analytical survey with a cross-sectional approach. The sampling technique used incidental sampling with a total of 36 women in reproductive age. Data analysis used Chi-Square test. Statistical results showed that there was a significant correlation between knowledge of women in reproductive age about cervical cancer and participation in early detection of cervical cancer, which is p value = 0.020 ( 0.05) and coefficient of contingency (r) = 0.423. The level of closeness of the correlation is medium. Therefore, there is a need for tailored services that could improve knowledge of women in reproductive age about cervical cancer to improve participation with a view to preventing cervical cancer by early detection.